Diastereoselective synthesis of functionalized diketopiperazines through post-transformational reactions - Balalaie, Saeed; Rominger, Frank (The journal of organic chemistry, 2017)
A diversity-oriented access to diastereoselective arylidene 2,5-diketopiperazines is elaborated via a sequential Ugi post-transformation involving catalytic cyclization and oxidative Heck reaction sequence. This sequence offers an interesting multicomponent entry to a library of 2,5-diketopiperazines and arylidene 2,5-diketopiperazines under mild reaction conditions in good to excellent yields.
Gesehen am 06.09.2018